Booster vaccination with a fractional dose of an oral cholera vaccine induces comparable vaccine-specific antibody avidity as a full dose: A randomised clinical trial. Issue 3 (16th January 2020) - Mottram, Lynda; Lundgren, Anna; Svennerholm, Ann-Mari; Leach, Susannah
Abstract: Antibody avidity is an important measure of the quality of vaccine-induced immune responses. Murine and human studies suggest that antibody avidity may be augmented by limiting access to antigen. The primary objective of this study was to evaluate in primed Swedish adults if booster vaccination with fractional doses (1/5th and 1/25th) of a model oral vaccine, the cholera vaccine Dukoral®, results in higher avidity antibody responses compared to boosting with a full vaccine dose. We also evaluated if fractional booster vaccination elicited similar magnitudes of antibody response compared to a full dose, and if the previously observed increase in antibody avidity after booster vaccination 1–2 years later occurred when boosting after a shorter interval. To this end, a randomised, open-label, exploratory Phase-II trial was performed. Swedish adults (n = 44), primed with two full doses of Dukoral®, were randomised into three groups and given a booster dose at either full (n = 14), 1/5th (n = 17) or 1/25th (n = 13) dose four months later. Antibody responses to cholera toxin B-subunit (CTB) were measured in serum and mucosal antibody in lymphocyte secretions (ALS). We found that the 1/5th and 1/25th booster doses had similar abilities as the full dose to induce significantly higher avidity anti-CTB antibody responses in both ALS and serum samples, as compared to after priming vaccination. There was a non-significant trend to lower magnitudes of ALS and serum IgA responses after the 1/5th compared to the full booster dose, and responses after the 1/25th dose were significantly lower. Our findings suggest fractional booster doses of Dukoral® four months after priming result in anti-toxoid mucosal antibody responses with increased antibody avidity compared to after priming vaccinations. ISRCTN registry identifier 11806026.